Effect of ferric carboxymaltose on calculated plasma volume status and clinical congestion: a FAIR‐HF substudy. (30th May 2019) - Okonko, Darlington O.; Jouhra, Fadi; Abu‐Own, Huda; Filippatos, Gerasimos; Colet, Josep Comin; Suki, Chainey; Mori, Claudio; Ponikowski, Piotr; Anker, Stefan D.; ,
Abstract: Aims: Iron deficiency worsens symptoms, quality of life, and exercise capacity in chronic heart failure (CHF) and might do so by promoting fluid retention. We assessed whether iron repletion improved congestion in CHF and appraised the prognostic utility of calculated plasma volume status (PVS), a novel index of congestion, in the FAIR‐HF data set. Methods and results: In FAIR‐HF, 459 iron deficient CHF patients were randomized to intravenous ferric carboxymaltose (FCM) or saline and assessed at 4, 12, and 24 weeks. Using weight and haematocrit, we calculated PVS in 436 patients. At baseline, PVS and weight were −5.5 ± 7.7% and 76.9 ± 14.3 kg, with peripheral oedema evident in 35% of subjects. Higher PVS values correlated to other congestion surrogates such as lower serum albumin. At 4 weeks, FCM was associated with greater reductions in weight (0.02) and PVS ( P < 0.0001), and a trend for improved peripheral oedema at 24 weeks (0.07). Irrespective of treatment allocation, patients with a decrease in PVS from baseline to week 24 had higher increments in 6 min walking distance (61.4 m vs. 43.5 m, 0.02) and were more likely to improve their NYHA class (33.3% vs. 15.5%, 0.001). A PVS > −4% at baseline predicted worse outcomes even after adjustment for treatment assignment (hazard ratio 1.88, 95% confidence interval 1.01–3.51, 0.046). Conclusions: Intravenous iron therapy with FCM is associated with early reductions in PVS and weight, implying that decongestion might be one mechanism via which iron repletion aids CHF patients. Calculated PVS is of prognostic utility in this cohort.